Organic Cotton in Sustainable Production (ModaPalavra e-periódico, 2014)
From research topics related to organic cotton, fashion and sustainability, this article presents importante issues to the understanding of the concept of sustainability applied to the fashion system and the textile sector. This article aims to present some solutions that can minimize negative environmental impacts and also contribute to social and economic benefits, taking direction to the planting of organic cotton in the current fashion system. Based on literature review, the following work was developed from the theories that exposes developed concepts of sustainability applied to fashion and consumption of clothing. Finally, this article presented examples of how professionals in the field of fashion are introducing sustainability concepts through the use of raw materials from organic cotton products and services.
Keywords: organic cotton; sustainability; fashion